Akańskie sposoby rytualnego rozwiązywania kryzysów - Wita, Grzegorz (Śląskie Studia Historyczno-Teologiczne, 2023)
A generally recognized function of religion in traditional communities has been seen in the integration of symbols and values around problems of communal and social order. Article presents the Akan approach to an issue of crisis and their ritual solutions. Ritual action is a mean by which its participants discover who they are in the world and how it is with the world. Rituals repeat the act which found the harmony on the earth and among men. Crisis ritual is performed occasionally at period of affliction. Whenever a catastrophe or an evil thing threatens the life of an individual or a community, the rituals are performed to ward off the evils and thereafter bring back the rhythm of life into its normal position. If a misfortune such as death, sickness, bareness occurs it demand searching for the cause of such disaster. On the next stage is a special healing ritual carried out in the form of exorcising spirits predicted to be responsible for the problem. Finally performed ritual brings reconciliation. Above article examines two crisis rituals: theft and witch cleansing. Such rites (as tutuw bo) among Akans are the practice by which culprits are exposed to shame, to ritual purification and absolve from their evil.